Interfaith Marriage Involving Muslims in Indonesia: Legal Pluralism and Maqāṣid al-Sharīʿah Perspectives - Ma'u, Dahlia Haliah; Wagiyem, Wagiyem; Salma, Salma; Taqwa, Ria Hayatunnur (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2025)
In the Indonesian Islamic and society context, legal pluralism and interreligious interactions have potential. However, the ongoing and legally interfaith marriage continues to create a paradox. In accordance, the study examines the legal framework of interfaith marriage within the national legal framework, the pluralism in the law, and the judicial system, where legal enforcement is judged by maqāṣid al-sharīʿah principles. With a normative legal approach, this analysis is grounded in primary statutory paradigms, Islamic codifications, secondary administrative laws, and judicial practices and doctrines. Within this context, interfaith marriage has been indicated as an illegal marriage, not legally recognized within the religious framework. Although legal pluralism historically rose to various judicial practices, in Islamic divorce law, considerable differentiation has been eliminated. In creating and maintaining a unified linear hierarchy, subordinate norms must follow the Religious Norms. From the maqāṣid perspective, this unequivocally represents the protection of the Religion, the Preservation of the Order (Siyasah Shariyyah regarding the Ashabiyyah), the Posterity (Nasal), the Soul (Ruh), and the Property (Mal). The findings of this study indicate that Indonesia's regulation of interfaith marriages illustrates the purposeful incorporation of the Islamic law goals into the state’s family law and the strengthening of legal and social order within a pluralistic context.